For White Social Workers: RE/UN/DIScover Heuristic for Dual Awareness in Ongoing Anti-Racist Practice - Keenan, Elizabeth (Advances in Social Work, 2023)
Although many White social workers engage in ongoing anti-racist actions, they may still be complicit in perpetuating and reinforcing racism and White Supremacy Culture. Black, Indigenous, and People of Color (BIPOC) social workers, activists, and scholars have described the numerous ways in which the harmful impacts of White Supremacy Culture appear in the well-intentioned efforts of White people who seek to be anti-racist. White social workers are thus responsible for engaging in intentional ongoing practices to identify, interrupt, and shift their interpersonal oppressive uses of power in their practice. The RE/UN/DIScover heuristic is an iterative, embodied set of three practices for working with one’s experiences of shame and internalized dominance, habitual not-seeing, and in-the-moment activations. Literature theorizing White Supremacy ideology and culture frames the description of the RE/UN/DIScover heuristic. This paper describes several heuristic applications, including prompts for engaging in REcover, UNcover and DIScover practices and two composite examples. These applications illustrate how to use the heuristic practices with dual awareness of self and one’s social work practice in the moment and over time. White social workers are encouraged to learn and use the RE/UN/DIScover heuristic practices to guide their efforts to more fully live into their anti-racist commitments in moments of not-seeing and moments of activation.
Number: 2
Keywords: Heuristic; Power; Social work practice; White social workers; anti-racist; dept.swk; peer-reviewed